Poly-ε-caprolactone microspheres containing interferon alpha as alternative formulations for the treatment of chronic hepatitis C (Brazilian Journal of Pharmaceutical Sciences, 2012)
Interferon-alpha (IFN-alpha) is one of the main drugs used in the treatment of hepatitis C. Use of IFN-alpha has some limitations that result in poor treatment efficacy and low patient compliance. Therefore, the aim of this study was to develop poly-ε-caprolactone (PCL) microspheres containing IFN-alpha as an alternative for the treatment of chronic hepatitis C. Microspheres were prepared using the multiple emulsion followed by solvent evaporation technique. Particle size, surface morphology, drug content and encapsulation efficiency of the microspheres produced were evaluated. The stability of the formulation was assessed after 90 days at -20ºC. An in vitro release study was performed in PBS. In vitro cytotoxicity of the formulation was studied using hepatic cell line. The freeze-dried microspheres had mean particle size, IFN-alpha content, and encapsulation efficiency of 38.52 ± 4.64 µm, 15.52 ± 3.28% and 83.93 ± 5.76%, respectively. There were no significant changes during storage and the structural integrity of the protein was not compromised by the preparation technique. A total of 82% of the IFN-alpha was released after 28 days and the developed microspheres did not present cytotoxicity to the hepatic cell line. In vivo studies are currently underway to evaluate the biological activity of IFN-alpha encapsulated into microspheres.